Proceedings of the 2011 ACM SIGCOMM Conference on Internet Measurement Conference 2011
DOI: 10.1145/2068816.2068842
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the initial DNS behavior of malicious domains

Abstract: Attackers often use URLs to advertise scams or propagate malware. Because the reputation of a domain can be used to identify malicious behavior, miscreants often register these domains "just in time" before an attack. This paper explores the DNS behavior of attack domains, as identified by appearance in a spam trap, shortly after the domains were registered. We explore the behavioral properties of these domains from two perspectives: (1) the DNS infrastructure associated with the domain, as is observable from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 10 publications
0
56
1
Order By: Relevance
“…We understand that previous work [3] investigates on initial DNS behaviors (e.g. registration of domains) of malicious domains and reports some interesting characteristics but does not propose a method to detect malicious domains.…”
Section: Comparison With Related Workmentioning
confidence: 94%
See 3 more Smart Citations
“…We understand that previous work [3] investigates on initial DNS behaviors (e.g. registration of domains) of malicious domains and reports some interesting characteristics but does not propose a method to detect malicious domains.…”
Section: Comparison With Related Workmentioning
confidence: 94%
“…Hao et al [3] studied behavior of spam domains combining with active DNS behavior and registration information. Although they found that IP spaces used by spam domains were small, how d, ns-d and IP were related was not studied.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their short lifetime, the early identification of phishing websites is paramount, as a result several methods have been proposed to avoid reactive blacklisting and develop more proactive methods. In [10], Hao et al analyze early DNS behavior of newly registered domains. It is demonstrated that they are characterized by DNS infrastructure pattern and DNS lookup patterns monitored as soon as they are registered, such as either a wide scattering of resource records across the IP address space in only few regions, or resource records that are often hosted in tainted autonomous systems.…”
Section: Related Workmentioning
confidence: 99%